Autophagy-dependent ferroptosis in kidney disease - Yang, Yuanting; Cheng, Jiayi; Lin, Qisheng; Ni, Zhaohui (Frontiers in Medicine, 2023)
Ferroptosis is a new type of cell death caused by the lack of glutathione peroxidase 4(GPX4) and the imbalance of cellular redox, which is characterized by the accumulation of lipid peroxidation on cell membrane. There are multiple regulatory pathways of ferroptosis, including GPX4 pathway, glutamate-cystine antiporter (System Xc-) pathway, lipid metabolism pathway and iron metabolism pathway. Recent studies have reported that autophagy-dependent ferroptosis (ferroptosis meditated by ferritinophagy, lipophagy and clockophagy) plays a significant role in the occurrence of many diseases, including nervous system diseases, liver diseases, lung diseases and kidney diseases. This review aims to overview the progress of research on the autophagy-dependent ferroptosis in kidney diseases.